The Digital Leadership Model for Administrators of Vocational Education in Kaifeng City Under Henan Province - Wang Chengwei; Tipanark , Peerapong; Muangman , Pornthep (Journal of Roi Kaensarn Academi, 2024)
As the digital transformation of higher education in China continues to deepen, traditional leadership urgently needs to expand and shift towards digital leadership. As vocational education is a vital part of higher education, there is an urgent need to enhance the digital leadership capabilities of its administrators. In Kaifeng City, Henan Province, vocational education administrators struggle with integrating digital technologies, which limits their ability to lead and innovate in a fast-changing digital environment. The objectives of this research were to: (1) Determine the components and sub-components of digital leadership for administrators of vocational colleges in Kaifeng City, Henan Province. (2) Propose a digital leadership model for these administrators. The study’s population comprised 4,576 principals, deans, student counselors, and teachers from vocational colleges in Kaifeng City, Henan Province, China. A stratified random sampling method was employed, resulting in a sample of 363 participants. Data were collected using a questionnaire, and analyzed with descriptive statistics (percentage, arithmetic mean, standard deviation), Exploratory Factor Analysis (EFA), and Confirmatory Factor Analysis (CFA) using statistical software. The research findings revealed: (1) Four key components and 13 sub-components of digital leadership, derived from the conceptual framework, were identified. The four components are digital communication, digital vision, digital innovation, and digital collaboration. (2) The proposed digital leadership model for administrators of vocational colleges was consistent with the empirical data: Chi-square (χ2) = 103.97, Relative Chi-square (χ2/df) = 2.00, Degrees of Freedom (df) = 52, Statistical Significance (p) = 0.00, Goodness of Fit Index (GFI) = 0.96, Adjusted Goodness of Fit Index (AGFI) = 0.92, and Root Mean Square Error of Approximation (RMSEA) = 0.05. Components ranged from 0.82 to 0.98, while the sub-components/sub-components ranged from 0.65 to 0.87. The study presents a validated digital leadership model specifically designed for vocational education administrators in Kaifeng City, Henan Province. By pinpointing and validating the essential components and sub-components of digital leadership, this research offers a practical framework that administrators can use to enhance their digital skills and lead their institutions more effectively in the digital era. This model provides a foundation for creating targeted professional development programs and strategic initiatives to promote digital leadership within vocational education settings.